2006
DOI: 10.1038/sj.jhh.1002065
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, obesity and cardiovascular function in African and Caucasian women from South Africa: the POWIRS study

Abstract: The integrated relationship between inflammation, obesity and cardiovascular disease is currently a subject of much research interest. These specific relationships, however, have not been studied in-depth in South African population groups in order to determine the role of ethnicity. It is known that Africans, compared to Caucasians, suffer from a high prevalence of hypertension. It was therefore hypothesized that the levels of inflammatory markers (high-sensitivity C-reactive protein (hsCRP), fibrinogen and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…66,67 White women have lower leptin levels than Black BMI-matched African women, 68 indicating an ethnic variation in the production of this adipokine. 69 A positive association between leptin and blood pressure in Black South African women has been observed, 70,71 and leptin also correlates with total cholesterol levels. 72 Vitamin D deficiency has been associated with cardiometabolic diseases; however, the evidence is inconsistent.…”
Section: Metabolic and Anthropometric Factorsmentioning
confidence: 99%
“…66,67 White women have lower leptin levels than Black BMI-matched African women, 68 indicating an ethnic variation in the production of this adipokine. 69 A positive association between leptin and blood pressure in Black South African women has been observed, 70,71 and leptin also correlates with total cholesterol levels. 72 Vitamin D deficiency has been associated with cardiometabolic diseases; however, the evidence is inconsistent.…”
Section: Metabolic and Anthropometric Factorsmentioning
confidence: 99%
“…20 In South Africa, African women had higher levels of leptin than Caucasian women, especially when adjusted for waist circumference (WC). 21 A Chilean study showed lower leptin levels in Mapuche natives than Caucasians 22 and we have shown that…”
Section: Introductionmentioning
confidence: 99%
“…The current issue of the Journal of Human Hypertension features an article by Schutte et al 21 on the topic of inflammatory markers and obesity in South African Caucasian and Black women. The study population comprises 102 Black and 115 Caucasian women, who were individually matched for age and body mass index (BMI).…”
mentioning
confidence: 99%
“…Inflammatory markers (leptin, high-sensitivity CRP and fibrinogen), obesity (BMI and waist circumference) and cardiovascular traits (blood pressures, triglycerides, high-density lipoprotein-C, cardiac output and total peripheral resistance) were measured, and the relationships between these factors assessed within and between ethnic groups. Schutte et al 21 conclude that the levels of inflammatory markers are higher in African women than in their Caucasian counterparts, even after adjustment for waist circumference. Furthermore, the relationships between inflammatory markers and cardiovascular outcomes are stronger in Black women compared with Caucasian women before adjustment for measures of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation